Report Conference on Environmental & Social Challenges of Mineral Intensive Growth in Odisha - Planning Commission (Planning Commission, 2008)
Odisha is first approaching to be an economic powerhouse in the post independence period. Thanks to the pro industrialization policy adopted by provincial govt. large no. of Multi National Companies (MNCs) along with some economic powerhouse are approaching with investment plans. Out of the 50 odd Memorandum of Understandings signed till date, a majority of them are in the sector of Iron and steel, mining, tourism, hydropower and thermal power. This opens up The window of opportunity for employment for skilled, semi skilled as well as non skilled workers as a whole. The state is also likely to generate good revenue in terms of duties and taxes.
Planning Commission Government of India
Planning Commission Government of India